2020
DOI: 10.21272/mmi.2020.2-22
|View full text |Cite
|
Sign up to set email alerts
|

Innovation Ecosystems for the Moldovan Small and Medium-Sized Enterprises

Abstract: In the last decades, the word 'innovation' can be heard more and more on the entrepreneurial side. It has a crucial role in satisfying the customers, competition with other companies, and increasing the turnover of the enterprises. SME's economic performance is directly affecting the national budget. Still, there is not a precise method of assessing and improving the innovation process at neither firm nor national level. The paper aims to analyze the current innovative performance of Moldovan SMEs. The analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…The existence of positive multilateral links between responsible management, financial sustainability, organizational performance has been empirically confirmed (El Amri et al, 2020), which proves the need for a comprehensive consideration of managerial, social, financial and environmental parameters in building a modern enterprise. On the other hand, it is determined that insufficient development of intellectual capital and lack of state support reduce the introduction of innovations by enterprises and the development of the innovation ecosystem (Ubreziova et al, 2020). That is why the most effective way to develop enterprises should be to balance their economic, environmental and human potential.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The existence of positive multilateral links between responsible management, financial sustainability, organizational performance has been empirically confirmed (El Amri et al, 2020), which proves the need for a comprehensive consideration of managerial, social, financial and environmental parameters in building a modern enterprise. On the other hand, it is determined that insufficient development of intellectual capital and lack of state support reduce the introduction of innovations by enterprises and the development of the innovation ecosystem (Ubreziova et al, 2020). That is why the most effective way to develop enterprises should be to balance their economic, environmental and human potential.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The enterprises in the system are mainly small-and medium-sized enterprises, and each SME spontaneously seeks and establishes external innovation cooperation relationships as in Figure 8. Ubreziova et al surveyed 150 SMEs in the Republic of Moldova, utilizing questionnaire surveys, and concluded that a weak EIE slows the development of enterprises and that the economic performance of SMEs directly affects the national budget [31]. Therefore, it is extremely important to build a strong SME innovation ecosystem.…”
Section: (A) Eies Without a Core Enterprise(s)mentioning
confidence: 99%
“…Enterprises with high service innovation intensity have stronger ecological-related capabilities than do those with low service innovation intensity [11]. (d) Suggestions for companies: Ubreziova et al conducted research on 150 small and medium-sized enterprises in the Republic of Moldova, pointed out that a weak innovation ecosystem and lack of high-quality workers slowed down the development of enterprises, and put forward several suggestions for business managers and high-level government organizations [31]. (e) Ecological stage perspective: based on an exploratory case study on the innovation eco-system of China's high-speed railway industry, some authors have identified three ecosystem stages, namely the technology accumulation period, the technology introduction period, and the independent innovation period [25].…”
Section: Emerging Research Directionsmentioning
confidence: 99%
“…governo estadual, embora muito criticado por uma boa parte dos entrevistados, pela falta de um projeto concreto para a inovação do estado, apresenta por outro lado um programa para o incentivo dos polos regionais de inovação e propôs um planejamento estratégico para o estado do Rio Grande do Sul entre os anos de 2019 e 2022. Nesse tocante, é importante mencionar queIsenberg (2016), Radicic, Pugh e Douglas (2020),Ubreziova et al (2020) e Valkokari (2015 reforçam em seus artigos a importância do governo não apenas como provedor financeiro, mas como propositor de ações estratégicas para desenvolver o ecossistema.Sendo assim, saindo da visão da Hélice Tríplice e passando para refletir sobre a Hélice Quádrupla, a sociedade civil no Rio Grande do Sul tem grande importância, principalmente no tocante às universidades comunitárias com atuação em boa parte do estado. Além disso, é preciso aprofundar a visão para autores como Markkula e Kune (2015) e Ranga e Etzkowitz (2013), que reforçam o governo como personagem chave de um ecossistema de inovação.…”
unclassified